1969
DOI: 10.1161/01.res.24.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Action Potential of the Prenatal Rat Heart

Abstract: Transmembrane action potentials were recorded from embryonic rat hearts at ages between 10& days of gestation and birth (21 to 22 days). The resting potential averaged 30 to 40 mv at IOJ2 days and increased to around 80 mv by birth. Two periods of rapid increase in resting potential were noted: 1) from 10^ to 13& days and 2) from 19M days of gestation to birth. The maximal upstroke velocity of the action potential increased as the resting potential increased. The duration of the ventricular and atrial action p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 17 publications
5
28
0
1
Order By: Relevance
“…Bernard and Gargouil (7) and Couch et al (8) have demonstrated an increasing resting potential and a decreasing action potential duration from 10 days gestation to birth (21 days). Iri addition, Bernard and Gargouil (7) have shown that at 10 days gestation the action potential amplitude and configuration are insensitive to tetrodotoxin at concentrations as high as 10"…”
Section: Discussionmentioning
confidence: 99%
“…Bernard and Gargouil (7) and Couch et al (8) have demonstrated an increasing resting potential and a decreasing action potential duration from 10 days gestation to birth (21 days). Iri addition, Bernard and Gargouil (7) have shown that at 10 days gestation the action potential amplitude and configuration are insensitive to tetrodotoxin at concentrations as high as 10"…”
Section: Discussionmentioning
confidence: 99%
“…Pacemaker precursor cells have been identified in the ventricular primordia of the chick heart (stage 4, 18-19 h of incubation) (17). Transmembrane potentials of all myocardial cells at this developmental stage and later depolarize spontaneously during diastole (14,(18)(19)(20). As development proceeds, spontaneous depolarization is observed in progres- sively fewer myocardial cells (3,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very likely that the a,-adrenoceptors are coupled to Ca" channels at an early stage of development and then shift to the Z, in the mature state. Another point is that ventricular myocytes from prenatal and newborn rats have an action potential with an elevated plateau similar to that of other mammalian species [21], while the action potential in adult rat ventricular cells has a duration of less than 100 ms [l]. The duration of the action potential is in part due to the influence of Ca".…”
Section: Discussionmentioning
confidence: 99%